The organisation of afferent input to the basal ganglia - Dalzell, MRR (2014)
The basal ganglia are a collection of interconnected subcortical nuclei involved in movement, association, motivation and reward processing. Two populations of neurons that play critical roles in the basal ganglia are dopaminergic neurons of the substantia nigra (SN) and neurons of the subthalamic nucleus (STN). To define the afferent input to these neurons, which ultimately controls their activity, quantitative immunocytochemical analyses of afferent synaptic terminals was carried out at the electron microscopic level in rat. Glutamatergic afferents from cortical and subcortical sources were identified using antibodies against vesicular glutamate transporters (VGluT1 and 2 respectively). In the SN, dopaminergic neurons were labelled using antibodies against tyrosine hydroxylase (TH). In the analysis of the STN, additional populations of afferent terminals were labelled using antibodies against vesicular GABA transporter (VGAT), vesicular acetylcholine transporter (VAChT) and TH. Synapses were also categorised on the basis of their membrane specializations into type-1 (putatively excitatory) and type-2 (putatively inhibitory). In the SN, differences in the ratio of type-1 and 2 synapses were seen between two functional sub-regions (pars compacta: SNc and pars reticulata: SNr). Dopaminergic dendrites in the SNc receive equal innervation from boutons forming type-1 and 2 synapses (53% vs 47%), whereas dopaminergic dendrites in the SNr receive mainly type-2 synapses (73% vs 27%). Type-1 synaptic boutons included both VGluT1- and VGluT2-positive boutons in the SNc, meaning cortical and sub-cortical glutamatergic neurons directly innervate dopaminergic neurons of the SNc. In the SNr only VGluT2-positive boutons were detected suggesting that SNr dendrites only receive sub-cortical glutamate. However, a large proportion of boutons forming type-1 synapses were not labelled (~40% of type-1 synaptic boutons) suggesting other transmitters provide a large amount of innervation to these neurons. In the STN type-1 and 2 synapses provided roughly equal innervation of dendrites. The boutons forming type-1 synapses were almost entirely either VGluT1- or VGluT2-positive boutons (98%) indicating that STN neurons receive input from both cortical and subcortical glutamatergic neurons. Significantly more boutons were immunolabelled with VGluT2 compared to VGluT1 (31% vs 18%), showing that subcortical sources provide the majority of glutamatergic input to STN neurons. VGAT-positive synaptic boutons were exclusively type-2 and made up ~89% of type-2 synapses, TH-positive boutons comprised only ~4% of total synapses and VAChT-positive boutons were more varied producing both type-1 and 2 synapses. Type-1 synapse forming VAChT-positive boutons comprised 4% of total synapses and type-2 synapse forming VAChT-positive boutons 6% of the total innervation. Together this totals over 100% suggesting at least two of these markers are co-localised within a subgroup of boutons. In conclusion, this study demonstrates that both dopaminergic neurons of the SN and neurons of the STN are under the afferent synaptic control of both cortical and sub-cortical glutamatergic neurons as well as GABAergic and other populations of terminals. The quantitative analyses demonstrate differences in the innervation of the different types or sub-types of neurons that likely underlie their functional properties.